PERSPEKTIF PELAKU UMKM DALAM UPAYA MENINGKATKAN KUALITAS PRODUK UNTUK MENCIPTAKAN KEPUASAN DAN LOYALITAS ( STUDI KASUS USAHA TAHU BAPAK MATNURI ) - Santoso, Edy; Hakimah, Ema Nurzainul; Ratnanto, Sigit (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2023)
This research focuses on the efforts made by Mr. Matnuri's tofu home industry in improving product quality so as to create customer satisfaction and loyalty. The aim of this research is to find out how to improve the quality of tofu products in achieving customer satisfaction. To find out whether the quality of the product can affect customer satisfaction. In this business, they always prioritize product quality. Currently, customers are increasingly selective and intelligent in making decisions because they are supported by product choices on the market. Business actors must find ways to retain their customers. Customer loyalty means a person's habit of buying products offered during the exclusive period and his loyalty following all the company's offers. To support the competitive strategy in terms of maintaining market share, decisions must be taken to increase product quality and customer satisfaction so as to attract customer loyalty in making purchasing decisions. The process of generating self-purchase satisfaction for everyone is essentially the same, however, the selection-making procedure will be accompanied by characteristics. In its development, every business actor will pay attention to the quality of the products being marketed. The research approach used in this study is a qualitative approach. The type of research used in this research is case study research. An in-depth, case study is an example that is comprehensive, intense, clearer, in-depth, and more focused as an effort to examine the latest problems or empirical. in qualitative research, researchers themselves or with the help of others are the main data collectors. In this case as stated by, the position of researchers in qualitative research. It is shown that the product was the same as the customer's expectations so it can be said that the customer is satisfied. To maintain customer satisfaction, business is the primary benchmark, namely the quality of tofu according to their expectations and how many customers have bought tofu, conveying customers use affordable prices so that customers feel that product quality has a significant effect on increasing customer loyalty.